2021
DOI: 10.3390/jcm10163685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thyroid Hormone Replacement Dosing in Morbidly Obese Hypothyroid Patients after Bariatric Surgery-Induced Weight Loss

Abstract: The most frequent endocrine disease in obese patients is hypothyroidism. To date, there are no clear data regarding what happens to the dose of levothyroxine (LT4) after bariatric surgery (BS). The objective of the present study was to evaluate thyroid hormone replacement dose in morbidly obese hypothyroid patients after BS-induced weight loss. We explore the best type of measured or estimated body weight for LT4 dosing. We performed an observational study evaluating patients with morbid obesity and hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…These result highly suggest that sleeve gastrectomy and a Roux-en-Y Gastric Bypass showed different changes in levothyroxine needs. However, in agreement with Pedro et al [ 77 ], our group study did not find the bariatric surgery technique to be a predictor of levothyroxine dose variation [ 94 ]. Similar results have been found by other authors; both sleeve gastrectomy and a Roux-en-Y Gastric Bypass improved thyroid function in the same way [ 90 ].…”
Section: Thyroid Hormone Treatment In Obese Patients With Hypothyroid...supporting
confidence: 91%
See 4 more Smart Citations
“…These result highly suggest that sleeve gastrectomy and a Roux-en-Y Gastric Bypass showed different changes in levothyroxine needs. However, in agreement with Pedro et al [ 77 ], our group study did not find the bariatric surgery technique to be a predictor of levothyroxine dose variation [ 94 ]. Similar results have been found by other authors; both sleeve gastrectomy and a Roux-en-Y Gastric Bypass improved thyroid function in the same way [ 90 ].…”
Section: Thyroid Hormone Treatment In Obese Patients With Hypothyroid...supporting
confidence: 91%
“…Other authors have found similar results with a decrease or no change in the total levothyroxine requirement, but an increase of the weight-based levothyroxine requirement after bariatric surgery [ 93 ]. Our group has encountered that, following bariatric surgery, the total levothyroxine or the levothyroxine dose/kg of IBW did not change; however, the levothyroxine dose/body surface area, levothyroxine dose/kg of actual BW, levothyroxine dose/kg of adjusted BW and levothyroxine dose/kg of LBW increased [ 94 ].…”
Section: Thyroid Hormone Treatment In Obese Patients With Hypothyroid...mentioning
confidence: 99%
See 3 more Smart Citations